2014
DOI: 10.1016/j.jallcom.2013.12.200
|View full text |Cite
|
Sign up to set email alerts
|

Annealing of RF-magnetron sputtered SnS2 precursors as a new route for single phase SnS thin films

Abstract: Tin sulphide thin films have been grown on soda-lime glass substrates through the annealing of RF-magnetron sputtered SnS 2 precursors. Three different approaches to the annealing were compared and the resulting films thoroughly studied. One series of precursors was annealed in a tubular furnace directly exposed to a flux of sulphur vapour plus forming gas, N 2 + 5%H 2 , and at a constant pressure of 500 mbar. The other two series of identical precursors were annealed in the same furnace but inside a graphite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…SnS 2 films often include secondary phases of Sn 2 S 3 or SnS, which may significantly affect the structural, optical, and electrical properties of the material [29,30]. One of the most effective methods of phase analysis of Sn x S y compounds is Raman spectroscopy [31,32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SnS 2 films often include secondary phases of Sn 2 S 3 or SnS, which may significantly affect the structural, optical, and electrical properties of the material [29,30]. One of the most effective methods of phase analysis of Sn x S y compounds is Raman spectroscopy [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most effective methods of phase analysis of Sn x S y compounds is Raman spectroscopy [31,32]. This method is mostly used together with XRD and allows one not only to study phase composition but also to identify polytypes in the samples [29,33].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the several weak peaks located at 252 cm -1 , 288 cm -1 , 350 cm -1 and 374 cm -1 were observed; these are known to result from a kesterite CZTS phase [29][30]. However, some literature surveys indicated that the Raman peaks located at 250 cm -1 and 288 cm -1 were overlapped both of CZTS and Cu and Sn-based secondary phase [31][32][33]. Based on our XRD results, they were secondary phases.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the very weak peaks located at 153 cm -1 (CF) and 165 cm -1 (RTA) were observed in the CZTS thin films, which resulted in the SnS compound [33]. Generally, it is well known that the penetration depth of 514 nm Raman excitation laser was ~ 100 nm.…”
Section: Characterization Of Czts Thin Filmsmentioning
confidence: 99%
“…This is why films of Sn x S y compounds usually contain secondary phases [3]. The SnS 2 -SnS phase transition has been studied only for thermal annealing [20]. At the same time, laser irradiation could be considered as an effective method for controllable phase transition in Sn x S y since it provides rapid increases of temperature in materials.…”
Section: Introductionmentioning
confidence: 99%